2009 42nd Hawaii International Conference on System Sciences 2009
DOI: 10.1109/hicss.2009.335
|View full text |Cite
|
Sign up to set email alerts
|

Open Access to Scientific Literature - Increasing Citations as an Incentive for Authors to Make Their Publications Freely Accessible

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Both of these qualitative and quantitative differences are statistically significant, but keep in mind that the accessibility of papers and artifacts are not independent: some conferences that encouraged artifacts were also open-access, particularly those with the ACM. Another dependent covariate with accessibility is citations; several studies suggested that accessible papers are better cited ( Bernius & Hanauske, 2009 ; Niyazov et al, 2016 ; Snijder, 2016 ), although others disagree ( Calver & Bradley, 2010 ; Davis & Walters, 2011 ; McCabe & Snyder, 2015 ). This dependence may explain part of the higher citability of papers with artifacts, as elaborated next.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these qualitative and quantitative differences are statistically significant, but keep in mind that the accessibility of papers and artifacts are not independent: some conferences that encouraged artifacts were also open-access, particularly those with the ACM. Another dependent covariate with accessibility is citations; several studies suggested that accessible papers are better cited ( Bernius & Hanauske, 2009 ; Niyazov et al, 2016 ; Snijder, 2016 ), although others disagree ( Calver & Bradley, 2010 ; Davis & Walters, 2011 ; McCabe & Snyder, 2015 ). This dependence may explain part of the higher citability of papers with artifacts, as elaborated next.…”
Section: Resultsmentioning
confidence: 99%
“…Among the many paper-related factors studied in relation to citations is the paper’s text availability, which our data shows to be also linked with artifact availability. there exists a rich literature examining the association between a paper’s own accessibility and higher citation counts, the so-called “OA advantage” ( Bernius & Hanauske, 2009 ; Davis & Walters, 2011 ; Sotudeh, Ghasempour & Yaghtin, 2015 ; Wagner, 2010 ).…”
Section: Related Workmentioning
confidence: 99%
“…A similar process is employed in other contexts, specifically the use of Game Theory (e.g. Hanauske, Bernius, & Dugall, 2007), and modelling of citation networks (Bernius & Hanauske, 2009). A quite different example is found in the use of Actor Network Theory (Cana, 2010;Rieger, 2008), which as discussed above constitutes both a theory of interaction and a research method.…”
Section: Theory Generationmentioning
confidence: 99%